Oxidative stress neuroinflammation and cellular stress response in sensorineural hearing loss: novel nutritional therapeutical approaches - Serra, Agostino; Cocuzza, Salvatore; Di Mauro, Paola; Licciardello, Luisa; Spinato, Giacomo; Gallina, S; Maiolino, Luigi (Progress in Nutrition, 2016)
This study is intended to validate the hypothesis that changes in the redox state of glutathione, the major endogenous antioxidant, associated with the abnormal expression and activity of cytoprotective vitagenes, which in normal conditions are expressed only at low level may represent a critical factor, involved in the physiopathological changes associated to degenerative damage occurring in cochlear diseases. Moreover modulation of stress responsive vitagenes by nutritional antioxidants can be an effective therapeutic strategy to minimize consequences of oxidative stress associated to the pathogenesis and course of sensorineural hearing loss. One therapeutic approach can be antioxidant substances, as cisteina and superoxide dismutase supplementation to burst vitagenes and confer neuroprotection. The damage caused in the inner ear by oxidative stress can induce apoptosis and necrosis of both the hair cells as neurons of the spiral ganglion. Reactive oxygen species (ROS) and free radicals are formed not only as by-products of various metabolic pathways but also for exposure to ototoxic substances such as aminoglycosides and cisplatin, for hypoxia/ischemia and to exposure to noise. Although the mechanism of production of ROS within the cochlea has not yet been precisely identified, it is conceivable that mitochondrial dysfunction and consequent burst in oxidative stress are major causative factors. Consistent with this notion, it is known that the base of the cochlea is more vulnerable to oxidative damage resulted from exposure to ototoxic substances than the apical portions. The difference in survival between the basal outer hair cells and the apical ones appear to be due to a significantly lower level of glutathione in the basal outer hair cells than the apical, a phenomenon that makes it easier basal cells vulnerable to damage from free radicals.